2009
DOI: 10.2340/00015555-0553
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Pruritus with the Selective Serotonin Re-uptake Inhibitors Paroxetine and Fluvoxamine: Results of an Open-labelled, Two-arm Proof-of-concept Study

Abstract: Chronic pruritus is difficult to treat and requires the evaluation of new therapeutic modalities. We initiated an open-labelled, two-arm prospective, proof-of-concept study applying two selective serotonin re-uptake inhibitors on a long-term basis. Paroxetine and fluvoxamine were tested in a total of 72 pruritic patients (27 men, 45 women, age range 28-88 years, mean age 59.2 years). The reduction in pruritus was evaluated by analysis of visual analogue scores and determination of the maximal antipruritic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(92 citation statements)
references
References 30 publications
3
80
0
8
Order By: Relevance
“…Paroxetine (20 mg/d) was reported to have a very good antipruritic effect in patients with polycythemia vera, psychogenic and paraneoplastic pruritus as well as in pruritus of non-dermatologic origin 49 . A recent study confirms that paroxetine and fluvoxamine have beneficial effects in different types of pruritus 50 . As severe cardiac and central nervous side effects like drowsiness, vertigo and fatigue have been described especially in elderly patients this therapy should be used with caution until ongoing studies have been completed.…”
Section: Antidepressantsmentioning
confidence: 78%
“…Paroxetine (20 mg/d) was reported to have a very good antipruritic effect in patients with polycythemia vera, psychogenic and paraneoplastic pruritus as well as in pruritus of non-dermatologic origin 49 . A recent study confirms that paroxetine and fluvoxamine have beneficial effects in different types of pruritus 50 . As severe cardiac and central nervous side effects like drowsiness, vertigo and fatigue have been described especially in elderly patients this therapy should be used with caution until ongoing studies have been completed.…”
Section: Antidepressantsmentioning
confidence: 78%
“…These studies assumed that SSRI show efficacy for pruritus associated with the central nervous system rather than the peripheral nervous system (Ständer et al 2009). In this study, fluoxetine showed no efficacy for pruritus in CAD by CA-DESI-03 and PVAS.…”
Section: Resultsmentioning
confidence: 99%
“…Tab. 1, [23]). In dieser Studie hatten 70% der Patienten Nebenwirkungen wie Schläfrig-keit, Müdigkeit, sexuelle Dysfunktionen etc., die bei 18 Patienten zur Beendigung der Therapie führten.…”
Section: Pruritustherapie Mit Tetrazyklischen Antidepressivaunclassified
“…Nur wenige dieser Studien untersuchten die Beschwerdesymptomatik gezielt mithilfe von visuellen Analogskalen oder evalulierten Fragebögen [17,21,22,23]. Ferner wurde der Großteil der Studien nicht placebokontrolliert durchgeführt.…”
Section: Zusammenfassende Beurteilungunclassified